(untitled) (The Agriculturists, 2018)
Effect of pre-storage fungicidal treatment on prevalence of seed-borne fungi and quality of onion (Allium cepa L.) seeds was evaluated under laboratory condition. Seeds were treated separately with five fungicides namely Bavistin 50 WP (Carbendazim) and Dithane M-45 (Mancozeb) @ 2.2 g/kg, Homai (Thiophanate) and Rovral (Iprodione) @ 2.0 g/kg and Provax-200 (Carboxin) @ 3.0 g/kg of seeds before storage. Prevalence of seed-borne fungi, percent seeds germination and vigor index were evaluated just before storage, 75 and 150 days after storage. Fungicides produced significant negative impact on seed-borne fungi and positive impact in maintaining quality during storage. Provax-200, Rovral, Dithane M-45 and Bavistin effectively reduced seed-borne fungi and performed better for germination and vigor of seeds. Seed treatment with Provax-200, Rovral, Bavistin or Dithane M-45 would therefore be suggested as effective fungicides to control seed-borne fungal infection and maintain better germination and vigor of onion seed in storage. The Agriculturists 2017; 15(2) 52-58